CHANGING BALANCES IN SOUTH CAUCASUS AFTER 44 DAYS WAR, KEY AZERBAIJAN AND KEY ZENGEZUR - ÖZMEN, Süleyman (SSD Journal, 2022)
The 44-Day War was a groundbreaking war that radically changed the existing practices and balances in the South Caucasus. After the collapse of the USSR on December 26th, 1991, Armenia unjustly occupied Nagorno-Karabakh and the surrounding areas of Lachin, Gubatli, Zangilan, Cebrayil, Fizuli, Agdam and Kelbajar with the support of Moscow. During these occupations, thousands of Azerbaijani Turkish women were brutally murdered, along with their children. As a result of this occupation by Armenia in violation of the rules of international law, Azerbaijan lost 20% of its territory. After that date, until the 44-Day War began, Armenia continued to violate the borders it had carried out unjustly and to make provocations that had the potential to start a total war. Finally, President of Azerbaijan Ilham Aliyev, in his speech at the United Nations (UN) General Assembly on September 25th, 2020, stated that a counter-attack would be launched within the boundaries of the right to self-defense. He also announced that this operation would be carried out in order to realize Azerbaijan’s vision of ending Armenia’s unjust occupation in the region. This honorable war, launched against a long-standing injustice, is the UN Security Council affirming that Armenia is an occupier and that the occupied territories belong to Azerbaijan, and at the same time calling on the Armenians to end the occupation; It is compatible with the four UN Decision “822, 853, 874, 884”. The war started against the Armenian occupation elements on September 27th, 2020, ended with the absolute victory of Azerbaijan on November 10th, 2020. According to the basic principles of international law; attacks to change the borders by using force are not allowed under any circumstances, and the use of force to protect the attacked country and people is considered within the boundaries of the “right to self-defense”. Hence the 44 Day War; Since it complies with the rules of International Law, the UN, the Council of Europe and the Organization for Security and Cooperation in Europe (OSCE), it does not have a legal problem. The changing world after the Cold War and the 2008 global economic crisis; It has brought up the changing security perceptions and the ongoing global and regional conflicts, changing balances, new alliances and new potential regional power actors. Considering these developments that took place after the millennium, we can say that Azerbaijan is an important “keyhole” country, especially in the Caucasus region, and by looking at its geographical location that provides an opening from Europe to Asia, and the key to the lock is Zangezur. In this study, especially after the 44-Day War, the changing balances and opportunities in the South Caucasus will be examined. In this context, the importance of the Azerbaijan and Zangezur corridor, which we describe as the key country that was the absolute winner of the 44- Day War, will be discussed.